Kant’s Robust Theory of Grace - Mariña, Jacqueline (Con-Textos Kantianos. International Journal of Philosophy, 2017)
In this paper I argue against two prevailing views of Kant’s Religion. Against commentators such as Michalson and Quinn, who have argued that Kant’s project in Religion is riddled with inconsistencies and circularities, I show that a proper understanding of Kant’s views on grace reveals these do not exist. And contra commentators that attribute to Kant at best a minimalist conception of grace (e.g., Wood 1991 and Pasternack 2014), I show that Kant’s view of it is remarkably robust. I argue that Kant works with three different conceptions of grace. These are: a) grace and the God within, b) grace and the transformation of the fundamental orientation, and c) grace that can be laid hold of; the first and the last play a significant role in his philosophy of religion.